Journey to the United States of North America = Viaje a los Estados Unidos del Norte de America - Zavala, Lorenzo de, 1788-1836 (Recovering the U.S. Hispanic Literary Heritage Project publication., 2005)
Presents a comprehensive analysis of the U.S. political culture written from a Mexican perspective, and describes the political and economic relationship between the two countries. Presented in English and Spanish.